Предмет: Алгебра,
автор: moyoceaaan
Сократите. С объяснением, пожалуйста!!!
Приложения:
![](https://files.topotvet.com/i/f59/f59980cecb21b6fee89e6fa6864a0e90.gif)
Ответы
Автор ответа:
0
раскрываем скобку в числителе, получаем:
(1-2sin(x)cos(x))/(sin(x)-cos(x))
расписываем 1=sin^2(x)+cos^2(x), получаем:
(sin^2(x)-2sin(x)cos(x)+cos^2(x))/(sin(x)-cos(x))=((sin(x)-cos(x))^2)/(sin(x)-cos(x))=sin(x)-cos(x)
(1-2sin(x)cos(x))/(sin(x)-cos(x))
расписываем 1=sin^2(x)+cos^2(x), получаем:
(sin^2(x)-2sin(x)cos(x)+cos^2(x))/(sin(x)-cos(x))=((sin(x)-cos(x))^2)/(sin(x)-cos(x))=sin(x)-cos(x)
Похожие вопросы
Предмет: Математика,
автор: ialykbarova
Предмет: Алгебра,
автор: Jrjxnjd
Предмет: Русский язык,
автор: Doge90
Предмет: История,
автор: cheremshenko
Предмет: История,
автор: Аноним